Kematangan vokasional dengan kecemasan dalam menghadapi dunia kerja pada mahasiswa tingkat akhir - Ahmad Zulfahmi; Devina Andriany (Cognicia, 2021)
The dynamics of problems faced by final year students do not only affect academic achievement but also anxiety in facing the future world of work. University graduates tend to experience career anxiety due to a lack of competence and minimum knowledge of career-related information. This study aims to determine the relationship between vocational maturity and anxiety in dealing with the world of work in final year students, using a correlational quantitative approach. The sample used in the study amounted to 154 people with the criteria of students currently working on their thesis and aged 21-24 years, while the sampling method used accidental sampling technique. The measuring instruments used in this study were the Indonesian Career Adapt-Abilities Scale and the Career Anxiety Scale. Analysis of research data was using Pearson product moment correlation analysis. The results showed that there was a significant negative relationship between vocational maturity and anxiety in facing the world of work in final year students. Keywords: Anxiety in facing the world of work, early adulthood, final year students, vocational maturity